Cloning and Expression of the dnaK Gene of Campylobacter jejuni and Antigenicity of Heat Shock Protein 70 - Thies, Frank L. (American Society for Microbiology, 1999)
Campylobacter jejuni is a leading cause of infectious diarrhea throughout the world. In addition, there is growing evidence that Guillain-Barré syndrome, an inflammatory demyelinating disease of the peripheral nervous system, is frequently preceded by C. jejuni infection. In the present study, the hrcA-grpE-dnaK gene cluster of C. jejuni was cloned and sequenced. The dnaK gene consists of an open reading frame of 1,869 bp and encodes a protein with a high degree of homology to other bacterial 70-kDa heat shock proteins (HSPs). The overall percentages of identity to the HSP70 proteins of Helicobacter pylori, Borrelia burgdorferi, Chlamydia trachomatis, and Bacillus subtilis were calculated to be 78.1, 60.5, 57.2, and 53.8%, respectively. Regions similar to the Escherichia coli ς(70) promoter consensus sequence and to a cis-acting regulatory element (CIRCE) are located upstream of the hrcA gene. Following heat shock, a rapid increase of dnaK mRNA was detectable, which reached its maximum after 20 to 30 min. A 6-His-tagged recombinant DnaK protein (rCjDnaK-His) was generated in E. coli, after cloning of the dnaK coding region into pET-22b(+), and purified by affinity and gel filtration chromatography. Antibody responses to rCjDnaK-His were significantly elevated, compared to those of healthy individuals, in about one-third of the serum specimens obtained from C. jejuni enteritis patients.